2019
DOI: 10.1002/alr.22320
|View full text |Cite
|
Sign up to set email alerts
|

The neuroplastic effect of olfactory training to the recovery of olfactory system in mouse model

Abstract: Background Several studies have reported the benefits of olfactory training (OT) in the olfactory nervous system of mouse models. Therefore, in this study we performed next‐generation sequencing to evaluate the effects of OT on mRNA sequencing in the olfactory area. Methods Mice in each group were administered 300 mg of 3‐methylindole per kilogram of mouse weight. The olfactory function was evaluated by a food‐finding test once a week. The olfactory neuroepithelium was harvested for histologic examination and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…21 The four odors were selected due to their proven training effects based on previous human and animal studies. 12,17 Each mouse was placed into a covered plastic case (width  length  height: 200  260  130 mm) containing one of the four odorants. Each mouse was exposed to each odorant for 1 minute with a rest period of 2 minutes between stimuli to prevent olfactory fatigue.…”
Section: Olfactory Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The four odors were selected due to their proven training effects based on previous human and animal studies. 12,17 Each mouse was placed into a covered plastic case (width  length  height: 200  260  130 mm) containing one of the four odorants. Each mouse was exposed to each odorant for 1 minute with a rest period of 2 minutes between stimuli to prevent olfactory fatigue.…”
Section: Olfactory Trainingmentioning
confidence: 99%
“…13 The olfactory system exhibits neuroplasticity via mechanisms that have been extensively investigated at the cognitive and cellular levels. [14][15][16][17] Elucidating the different mechanisms underpinning steroid treatment and OT in olfactory loss will facilitate the application of treatments for olfactory disturbances with various clinical causes. The purpose of this study was to evaluate the different mechanisms of steroid therapy and olfactory training using experimental approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment outcomes were evaluated by both behavioral testing and RNA expression. The study demonstrated more rapid recovery of olfactory function in the olfactory training group, as well as upregulation of the genes associated with neurogenesis, providing additional support for the practice of olfactory training …”
mentioning
confidence: 58%
“…Notwithstanding what could be interpreted as marginal mechanistic evidence in human studies, the efficacy of olfactory training is supported by a small number of animal experiments. Kim et al 13 . evaluated olfactory recovery in olfactory‐lesioned mice via a food‐finding test and simulated olfactory training using common odorants over a period of 3 weeks 13 .…”
mentioning
confidence: 99%
“…Kim et al 13 . evaluated olfactory recovery in olfactory‐lesioned mice via a food‐finding test and simulated olfactory training using common odorants over a period of 3 weeks 13 . Olfactory training improved olfactory recovery time and was accompanied by changes in gene transcriptional pathways associated with neurogenesis.…”
mentioning
confidence: 99%